Pelatihan Antropometri Dan Pemanfaatan Teknologi Artificial Intelligence Dalam Pemantauan Status Gizi Balita Di Posyandu - Tjut Awaliyah Zuraiyah; Honifa Honifa; Lala Jamilah; Ridho Gusti Mardotilah (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2026)
Indonesia had long been placed among countries with a high prevalence of stunting, particularly within the population of children under five years of age. At Posyandu Permata Hati RW 12, the recording of children's anthropometric data still relied on conventional methods that were prone to errors and slowed down the process of identifying nutritional problems. This community service program was designed to strengthen the competence of posyandu cadres in monitoring children's nutritional status through two primary approaches: training in anthropometric measurement techniques based on World Health Organization standards and the implementation of an artificial intelligence-based application. The program consisted of information dissemination sessions, structured practice, and direct mentoring involving six active cadres and thirty-five guardians of children under five. Success was measured using pre- and post-tests, direct observation of practical skills, and participant satisfaction questionnaires. Findings indicated that cadres' understanding improved by 35%, nine out of ten cadres were able to operate the application independently, and the time required for data recording was reduced by up to 30% compared to the previous method. In addition, more than 80% of cadres reported greater confidence in interpreting and communicating nutritional status assessment results to the families of young children. The integrated program combining standardized training and digital technology proved capable of enhancing both the technical proficiency and communication skills of cadres, while contributing to the accuracy and efficiency of children's growth data recording.